PERAN GURU AGAMA KATOLIK DALAM MENANAMKAN NILAI-NILAI BUDI PEKERTI KEPADA SISWA SMA DI KOTA KUPANG - Emilai Barek Ola; Hemma Gregorius Tinenti; Thomas Kuslin (CREDENDUM: Jurnal Pendidikan Agama, 2026)
This study explores the perceptions of Catholic religion teachers and students regarding the implementation of Catholic religious education in schools and the challenges in fostering students’ character development. The research was conducted in four senior high schools in Kupang City, involving four Catholic religion teachers and 276 students. A mixed-method approach was used through structured interviews and questionnaire surveys. The findings reveal that Catholic religious education not only emphasizes doctrinal knowledge but also focuses on forming noble character and Christian values, including honesty, responsibility, discipline, respect, and care. Teachers serve as educators, spiritual guides, and role models by integrating moral values into classroom learning and extracurricular religious activities. Students generally expressed positive perceptions, acknowledging that teachers provide exemplary behavior, guide moral development, and encourage tolerance and ethical awareness. Several challenges were identified, such as limited facilities and learning resources, low student interest in religious subjects, the small number of Catholic students in public schools, and administrative workloads that reduce preparation time. Despite these obstacles, teachers remain committed and adaptive in creating meaningful learning experiences. The study highlights the importance of institutional support, improved facilities, relevant teaching materials, reduced administrative burdens, and contextual, technology-based learning strategies to strengthen character formation through Catholic religious education.